The meaning of tradition in the modern world: Village representatives in Poland - Institution in transition - Ilona Matysiak (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
The main aim of this paper is to discuss the current situation of village representatives (so±tysi) in Poland in the times of dynamic changes taking place in the Polish countryside in the last decades. The importance of the institution of village representatives manifest itself in two main dimensions. Firstly, it is supported by the power of tradition - village representatives are deeply rooted in the historical evolution of rural self-government in Poland. Secondly, this institution is a part of the current system of local democracy. Secondly, this institution is a part of the current system of local democracy. Due to the pressure to implement the bottom-up models of governance, the full potential of this institution should be realized and discussed. This discussion is based on the small-scale quantitative data from the surveys conducted among the village representatives and also the inhabitants, which gives the opportunity to confront both perspectives. It occurs, that, in the changing reality, the institution of village representative should be supported with more than just the forces of tradition.
Keywords: 330; village representatives; rural changes; the role of tradition